Regrowth of Napier Grass (Pennisetum purpureum Schumach) with the Bio-pore Infiltration Hole in the Tropical Riparian Moonson Region - Bahrani; Rusmayadi, Gusti; Zulhidiani, Rahmi (Journal of Agriculture and Applied Biology, 2020)
Technology water and rainfall in doing to reduce soil water deficit in the soil. The technology is bio-pore that formed living things, such as soil fau-na and crop roots. This study uses a single factor randomized block design environment (RBD). The factor studied was the Bio-pore Infiltration Hole (BIH), which is filled with organic matter. The treatment was repeated 4 times, so that 20 experimental units were obtained. The treat-ments consisted of A (without BIH) as a control, B (BIH + Dry leaves), C (BIH + cow dung), D (BIH + chicken manure), and E (LR B + cow manure). Napier grass cropped with a spacing of 50 x 50 cm2 that was observed for variables of crop height, wet weight and dry weight of crops per bun-dle. The ground water content is measured with soil boring, and rainfall is measured with an ombro-meter. The study was conducted in the Experi-mental Garden of the Faculty of Agriculture, Sei Riam Village, Pelaihari Sub-district, Tanah Laut Regency, with a time of 2 months from November to December 2019. Rainfall in November and December was 127.85 mm and 637.8 mm with uneven distribution. The ground water content in treatments BIH + cow dung, BIH + cow dung, BIH + chicken manure, and BIH + cow manure is different from without BIH because it is without or-ganic matter so that its ability to retain water is small and its content is also less. Growth of crop height variable between 187.16 to 191.85 cm, wet weight in the range of 12.1 kg / m2 - a 14.9 kg / m2, and the dry weight in the range of 3.9 kg / m2 - 4.6 kg / m2, so treatments B, C, D, and E gave the best response compared to A which generates crop height about 172.78 cm, 7.3 kg / m2 wet weight and 2.4 kg / m2 dry weight.